1995
DOI: 10.1128/jvi.69.9.5437-5444.1995
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for efficient amplification of whole hepatitis B virus genomes permits rapid functional analysis and reveals deletion mutants in immunosuppressed patients

Abstract: Current knowledge of hepatitis B virus (HBV) sequence heterogeneity is based mainly on sequencing of amplified subgenomic HBV fragments. Here, we describe a method which allows sensitive amplification and simplified functional analysis of full-length HBV genomes with or without prior cloning. By this method, a large number of HBV genomes were cloned from sera of six immunosuppressed kidney transplant patients. Two size classes of HBV genomes, one 3.2 kb and another about 2.0 kb in size, were found in all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
257
0
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(269 citation statements)
references
References 27 publications
8
257
0
4
Order By: Relevance
“…A previous study has demonstrated that linear monomeric HBV genomes with SapI ends can initiate a full replication cycle, leading to viral antigen expression. 20 Our results showed that pSuper/HBVS1 could also suppress expression of HBsAg and HBeAg of HBV genotypes B and C from clinical isolates to a similar extent as on a laboratory clone of genotype A ( Figure 5).…”
Section: Psuper/hbvs1 Suppresses Expression Of Hbv Clinical Isolates supporting
confidence: 57%
See 2 more Smart Citations
“…A previous study has demonstrated that linear monomeric HBV genomes with SapI ends can initiate a full replication cycle, leading to viral antigen expression. 20 Our results showed that pSuper/HBVS1 could also suppress expression of HBsAg and HBeAg of HBV genotypes B and C from clinical isolates to a similar extent as on a laboratory clone of genotype A ( Figure 5).…”
Section: Psuper/hbvs1 Suppresses Expression Of Hbv Clinical Isolates supporting
confidence: 57%
“…19 To clone the full-length HBV genome from clinical samples, a method described by Gunther et al was used. 20 After amplication, PCR products were purified and cloned into the vector yT&A (Yeastern Biotech Co., Shijr, Taiwan).…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV DNA was extracted from 200 μl of serum samples using a commercial viral DNA extraction kit (OMEGA, USA). The full-length HBV genome was amplified by polymerase chain reaction (PCR) using the primers and thermocycling conditions described by Günther et al (1995). The PCR product was digested with SapI (MBI, USA) and then ligated into the SapI-digested and shrimp alkaline phosphatase-treated pHY106 plasmid, producing a recombinant clone termed pHY106-HBV.…”
Section: Isolation and Sequence Analysis Of Clinical Hbv Strainsmentioning
confidence: 99%
“…To amplify the full sequence of the HBV genome, two pairs of synthetic oligonucleotide primers (p1, p2 and p3, p4) were used. PCR was carried out according to the methods described previously, (12) with LA Taq (TaKaRa Bio Inc., Ohtsu, Japan) for 40 cycles in the first PCR and 35 cycles in the second PCR. The sequences between the joint points of the amplified PCR fragments were amplified using the precore/core primers (p5, p6 and p7, p8).…”
mentioning
confidence: 99%